2022
DOI: 10.1039/d2qi00364c
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-rich graphene supported electrocatalysts synthesized by radio-frequency plasma for oxygen evolution reaction

Abstract: Transition metals and their compounds supported on graphene are promising electrocatalysts for applications. Their catalytic performance is benefitted from the vacancy defects of these electrolytes. However, the facile and effective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…2d and Table S1, ESI†), which benefited both the catalytic active site exposure and the fast mass transport. 66…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d and Table S1, ESI†), which benefited both the catalytic active site exposure and the fast mass transport. 66…”
Section: Resultsmentioning
confidence: 99%
“…2d and Table S1, ESI †), which benefited both the catalytic active site exposure and the fast mass transport. 66 XPS was performed to gain deep insight into surface chemical composition and interactions between active species. single atom sites in carbon backbones.…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
“…Therefore, it is of great practical significance to develop efficient, cheap and stable electrocatalysts to replace traditional noble metal catalysts. 9–13…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great practical signicance to develop efficient, cheap and stable electrocatalysts to replace traditional noble metal catalysts. [9][10][11][12][13] In recent years, researchers have done a lot of work on nonprecious metals and non-metallic electrocatalysts, and many new and efficient electrocatalysts have also been successfully developed, including transition metal oxides, transition metal suldes, transition metal nitrides, non-metallic doped carbon materials, etc. [14][15][16][17][18][19][20][21] The discovery and research of non-metallic electrocatalysts have opened up a new way and direction to replace noble metal electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Defect engineering is effective in adjusting the chemical environment of reactive active sites and the coordination valence state of electrocatalysts. The introduction of vacancy defects on electrode surface helps facilitates the formation of unsaturated metal centers that can improve the intrinsic activity of reaction sites. According to the existing reports, the preparation methods of cation-rich vacancy layered hydroxides include plasma stripping, high-temperature reduction, etching, and aprotic solvation, which induce metal cation leakage and vacancy defect production. , For example, an efficient radio-frequency plasma treatment strategy has been employed by He et al to achieve sulfur vacancies and oxygen vacancies in electrocatalysts, and the vacancy structure can effectively improve the OER properties of the material. Wang et al reported a NiFe-LDH containing a Ni 2+ vacancy constructed from Cu-NiFe-LDHs by using a coordination solution containing an organic molecule CH 3 NCS; this defective NiFe-LDHs showed significant electrocatalytic activity compared with original NiFe-LDHs.…”
Section: Introductionmentioning
confidence: 99%